ANALISIS PERBEDAAN MAKNA DALAM KATA SOUNA DAN SOUNI PADA KALIMAT BAHASA JEPANG - I Wayan Muliawan; I Wayan Wahyu Cipta Widiastika (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2026)
Language is a useful communication tool for humans, to exchange information, convey a thought, language can also be a regional identity and cultural identity. Therefore, it is very important for humans to know and understand the rules, aspects, and meanings contained in language and sentences. This study aims to determine the differences in the words souna and souni which are words from Japanese. By applying qualitative descriptive methods, it is used to dissect a problem to find answers and get conclusions from the study. The theory used in this study is the theory of contextual meaning according to Pateda, (2010: 116) which states that contextual meaning or situational meaning, situational meaning arises as a result of speech and context, The results of the study found that souna and souni have different grammatical forms. Souna works as a noun modification in other words souna is used to explain nouns that change verbs or adjectives into attributes explaining nouns. While souni is an adverbial form or verb modification its use is to explain verbs and usually shows the way or state when something is done or how something happens. Analysis of the meaning of the sentence of the word souna and souni contextual meaning also plays a role, in the analysis as explained the meaning of the sentence containing the word souna and souni has different meanings according to its contextual meaning. So in this study found that the difference between the words souna and souni is in its grammatical form or bunpo rules and the meaning of souna and souni depends on the context contained in the sentence analyzed with the theory of peteda.